Effect of Imiquimod on Cytokine Induction in First Trimester Trophoblasts - Jerry M. Manlove-Simmons; Fadi M. Zaher; Mark Tomai; Bernie Gonik; David M. Svinarich (Hindawi Limited, 2000)
Objectives: Imiquimod (IQ) is used clinically for the topical treatment of external genital warts. IQ is an immune response modifier and induces the expression of interferon-α and other cytokines in human Peripheral Blood Monocytes (PBMC). Trophoblasts have been previously shown to express inflammatory cytokines upon lipopolysaccharide (LPS) stimulation. The objective of this study was to evaluate the ability of IQ to induce transcription of cytokines in trophoblasts.